Childhood motor performance is increased by participation in organized sport: the CHAMPS Study-DK - Vallence, A.-M.; Hebert, J.; Jespersen, E.; Klakk, H.; Rexen, C.; Wedderkopp, N. (Scientific Reports, 2019)
Evidence suggests that motor performance in children is declining globally. We tested whether participation in organized sport is associated with motor performance, and estimate the effect of 30 months participation in organized sport on motor performance. Study participants were 1067 primary school students, enrolled in the Danish Childhood Health, Activity, and Motor Performance School study. Participation in organized sport was reported via text messaging. Coordination-related motor performance composite, fitness-related motor performance composite, and total motor performance composite were calculated. Data were analyzed using Generalized Estimating Equations. Participation in organized sport was positively associated with motor performance (all composites) in models that did and did not control for baseline motor performance. For models that did not control for baseline motor performance, this equated to 2-6% increases in motor performance per weekly sport session; for models that did control for baseline motor performance, this equated to 1-5% increases in motor performance per weekly sport session. Positive associations between participation in organized sport and motor performance identify participation in organized sport as a way to improve motor performance in children. These results might provide the basis to determine whether participation in organized sport could be beneficial for children with developmental movement disorders.